(untitled) (Global Journal of Science Frontier Research, 2020)
Area preference of three GPS tagged re-introduced tigresses (viz. ST3, ST9 and ST10) within their home ranges (MCP100%) was done in Sariska tiger reserve (STR). The exercise was based on their point locations using GIS technology for the period of 2018-19. The observed percentage of period spent in dense forest area (ST3=91%, ST9=72.2% & ST10=93.2%) shows the preference for the dense forest as compared to the degraded forest and human settlement areas or agriculture fields within the STR. The present study further demonstrates the role of terrain, especially deep valleys/gorges and availability of perennial water sources as factors responsible for area preference by tigresses. Identification of such spots preferred by tigers in the reserve, their mapping and according maximum protection from anthropogenic interferences is recommended.